PEMBERDAYAAN REMAJA MELALUI SPEAR (SCHEDULING PROGRAME: EDUKATIF ATRAKTIF REMAJA) BERBASIS TEORY PLANNED BEHAVIOUR - Dina Istiana; Rukmini Rukmini; Riska Jeje Nur'aini; Putri Sukma Rahayu (PPM STIKES Adi Husada, 2025)
Introduction & Aim: The younger generation is seen as the future of the nation, bringing hope and continuing the struggle towards a dignified Indonesia. Therefore, young people are an important asset and a fundamental human resource for future development. The objective of this community service is to apply youth empowerment through SPEAR (Scheduling Program: Attractive Education for Youth) based on the Theory of Planned Behavior. Implementation Methods: The activities carried out were health education, pre-test and post-test games, and how to fill out a daily schedule. The group divided into smaller groups before conducting the pre-test, which was in the form of a game consisting of several questions about reproductive health, drugs, and bullying. After playing the game, the group continued with a presentation of material related to the SPEAR program, followed by a video related to the pre-test game conducted at the beginning and a presentation of material by the group. The group conducted a post-test with a game similar to the one at the beginning. Activity Results: The data generated through the pre-test and post-test showed an improvement, with the final post-test results being 100% good (25 people), whereas the pre-test results were 13 people (52%) below standard, 6 people (24%) adequate, and 6 people (24%) good. With the correct category valued at 2 and the incorrect category valued at 1. Discussion: This program should not be limited to one period only, but should be carried out continuously.